Changes in weed species composition in irrigated agriculture in Saharan Algeria. (1st October 2018) - Eddoud, A; Buisson, E; Achour, L; Guediri, K; Bissati, S; Abdelkrim, H
Summary: This work characterises the changes in composition of the weed flora commonly associated with certain south‐eastern Algerian crops over a 20‐year period. Vegetation sampling was carried out between 1990 and 2010 in three 1 ha date palm plantations that do not have understory crops, six 400 m² glasshouses used for market gardening and three 30 ha cereal centre‐pivot irrigation plots. In total, 162 species belonging to 40 families were recorded. As in many other agroecosystems around the world, the dominant families were Poaceae, Asteraceae, Brassicaceae and Amaranthaceae representing 45.1% of the species identified. The weed communities were characterised by a set of species from various origins: species with biregional, triregional and multiregional origins, and Saharo‐Arabian and Mediterranean species were particularly well represented. Overall, the most common weed species were as follows: Chenopodium murale, Lolium multiflorum, Melilotus indicus, Lysimachia arvensis, Sonchus oleraceus, Setaria verticillata, Polypogon monspeliensis and Erigeron canadensis, all of which are therophytes. The weed flora differed among the three sampled agroecosystems, which is to be expected, as their respective management sequences are quite different. Weed monitoring over the 20 years showed that weed composition changed over time, particularly in the palm plantations and the cereal plots. For a better understanding of the drivers of weed composition and changes over time and better weed management, studying weed provenance (crop seed purchase and organic fertilisation) as well as agricultural practices is necessary.